2022
DOI: 10.15537/smj.2022.43.5.20220018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a low dose of empagliflozin on short-term outcomes in type 2 diabetics with acute coronary syndrome after percutaneous coronary intervention

Abstract: ‫دخول‬ ‫إعادة‬ ،)p=0.598 ‫%2.4؛‬ ‫مقابل‬ ‫األوعية‬ ‫تكوين‬ ‫وإعادة‬ ،)p=0.433 ‫%7.8)؛‬ ‫مقابل‬ 4.5%( ‫املستقرة‬ ‫غير‬ .)p=0.312 ‫%0؛‬ ‫مقابل‬ 2.2%( ‫التاجية‬ Objectives: To study the effects of low dose of empagliflozin on improving outcomes in diabetic patients with acute coronary syndrome )ACS( after percutaneous coronary intervention )PCI(. Methods: This double-blind controlled clinical trial was carried out on 93 diabetic patients )56 males and 37 females, mean age of 56.55 years( with ACS who underwent PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The study selection process is shown in Figure S1. We identified a total of 1483 records, and 25 reports were included in the final analysis. , Two publications were from the same original study and their data were pooled. , Thus, 24 studies, including 15 RCTs and 9 observational studies, were included. These studies were published between 2019 and 2023 and enrolled a total of 12,413 patients (6175 in the SGLT2i group and 6238 in the non-SGLT2i group).…”
Section: Resultsmentioning
confidence: 99%
“…The study selection process is shown in Figure S1. We identified a total of 1483 records, and 25 reports were included in the final analysis. , Two publications were from the same original study and their data were pooled. , Thus, 24 studies, including 15 RCTs and 9 observational studies, were included. These studies were published between 2019 and 2023 and enrolled a total of 12,413 patients (6175 in the SGLT2i group and 6238 in the non-SGLT2i group).…”
Section: Resultsmentioning
confidence: 99%
“…However, long-term empagliflozin administration did not significantly improve LV function, shape, adiposity, or diffuse fibrosis in individuals with T2DM [ 142 ]. Similarly, no significant difference in mortality was observed between patients with diabetes receiving low-dose empagliflozin after percutaneous coronary intervention (PCI) for ACS and the placebo group [ 143 ]. Nonetheless, empagliflozin treatment improved heart function in mice with diabetes after infarction, particularly diastolic function, suggesting potential benefits in diabetic cardiomyopathy [ 144 ].…”
Section: Novel Drugs and Their Anti-fibrotic Rolementioning
confidence: 99%
“…There was no significant difference between the empagliflozin group and the placebo group in terms of post-treatment cardiovascular mortality (2.2% vs 4.2%; P = 0.598), rehospitalization for unstable angina (4.5% vs 8.7%; P = 0.433), or coronary revascularization (2.2% vs 0%; P = 0.312). The results of this study showed that the addition of empagliflozin to standard care after percutaneous coronary intervention in patients with T2D complicated with acute coronary syndrome did not significantly reduce cardiovascular outcomes within 6 mo[ 47 ].…”
Section: Amimentioning
confidence: 99%